Preparation of the recycled and regenerated mesocarbon microbeads-based solid acid and its catalytic behaviors for hydrolysis of cellulose. (December 2018) - Li, Heng-Xiang; Zhang, Xiaohua; Wang, Qun; Zhang, Kang; Cao, Qing; Jin, Li'e
Graphical abstract: Highlights: Solid acid with high acid density can be prepared using MCMB with good properties. MCMB-based solid acid exhibited excellent catalytic ability for cellulose. MCMB-based solid acid demonstrated good recyclability and regeneration abilities. The yield of TRS of hydrolysis reached 66.7% for pretreated cellulose. Abstract: Mesocarbon microbeads (MCMB) from coal tar pitch have excellent mechanical strength, high density, and good thermal stability. Moreover, a great deal of aromatic constituents occur on its surface, favoring the substitution reaction of sulfonic group. Results showed that the total acid and –SO3 H amount was 4.36 mmol/g and 2.18 mmol/g, respectively. Moreover, the yield of total reducing sugar (TRS) and conversion ratio ( C r) for pretreated cellulose (DP = 101.5) can reach 66.7% and 68.8% at 140 °C for 240 min in distilled water, respectively. After four recycles, the TRS and C r decreased by 12.6% and 10.2%, respectively. Through the secondary and third regeneration for the catalyst, acid density still reached 88.1% and 87.2% of the initial R1 –MCMB–SO3 H, demonstrating excellent regeneration ability and recyclability of the solid acid. Therefore, MCMB-based solid acid exhibits an attractive potential in the conversion of cellulose into platform chemical compounds.